EVALUASI PERLAKUAN NITRIDASI GAS TEMPERATUR TINGGI TERHADAP STRUKTUR MIKRO, KEKERASAN DAN KETAHANAN AUS BAJA TAHAN KARAT AUSTENIT 316LVM - Agus Suprihanto (ROTOR, 2017)
High temperature gas nitriding for austenitic stainless steel 316LVM is successfully done. Specimens are treated at temperature 1323, 1373 and 1573 K for 15 minutes holding time at 0.3 atm nitrogen gas pressures. The effect of nitriding treatments on the hardness, wear resistance and microstructure are evaluated using Buehler microhardness tester, Ogoshi universal wear test machine and light optical microscop respectively. The results shows that hardness, wear resistance and grain size increase with treatments temperature. Keywords: high temperature gas nitriding, 316LVM, hardness, wear, grain size